Draft Eleventh Five Year Plan (2007-12) and Annual Plan 2007-08 (Sectoral Plans) Volume-II Government of Nagaland - Planning Commission (Planning Commission, 2007)
Set-up in 1968 as an evaluation and monitoring unit under the Planning & Co-ordination Department, it is now a full fledged Directorate w th District Evaluation Offices in seven districts at Kohima, Mokokchung, Mon, Phek, Tuensang, Wokha and Zunheboto. Functions: The main function of the Evaluation Directorate is to undertake independent unbiased evaluation studies on implementation of the various schemes/programmes of the Government and suggest ways and means to bring about improvement in their formulation and execution. Through the two aspects(i) retrospective-assessment of the achievement of the programmes and (ii) prospective -what should be done to improve the programmes and through cost-benefit analysis the evaluation studies aid decision making and provide insight into the programmes.
Planning and Co-Ordination Department Nagaland